Hot Spring Microbial Community Composition, Morphology, and Carbon Fixation: Implications for Interpreting the Ancient Rock Record - Schuler, Caleb G.; Havig, Jeff R.; Hamilton, Trinity L. (Frontiers in Earth Science, 2017)
Microbial communities in hydrothermal systems exist in a range of macroscopic morphologies including stromatolites, mats, and filaments. The architects of these structures are typically autotrophic, serving as primary producers. Structures attributed to microbial life have been documented in the rock record dating back to the Archean including recent reports of microbially-related structures in terrestrial hot springs that date back as far as 3.5 Ga. Microbial structures exhibit a range of complexity from filaments to more complex mats and stromatolites and the complexity impacts preservation potential. As a result, interpretation of these structures in the rock record relies on isotopic signatures in combination with overall morphology and paleoenvironmental setting. However, the relationships between morphology, microbial community composition, and primary productivity remain poorly constrained. To begin to address this gap, we examined community composition and carbon fixation in filaments, mats, and stromatolites from the Greater Obsidian Pool Area (GOPA) of the Mud Volcano Area, Yellowstone National Park, WY. We targeted morphologies dominated by bacterial phototrophs located in close proximity within the same pool which are exposed to similar geochemistry as well as bacterial mat, algal filament and chemotrophic filaments from nearby springs. Our results indicate i) natural abundance δ13C values of biomass from these features (-11.0 to -24.3 ‰) are similar to those found in the rock record; ii) carbon uptake rates of photoautotrophic communities is greater than chemoautotrophic; iii) oxygenic photosynthesis, anoxygenic photosynthesis, and chemoautotrophy often contribute to carbon fixation within the same morphology; and iv) increasing phototrophic biofilm complexity corresponds to a significant decrease in rates of carbon fixation—filaments had the highest uptake rates whereas carbon fixation by stromatolites was significantly lower. Our data highlight important differences in primary productivity between structures despite indistinguishable δ13C values of the biomass. Furthermore, low primary productivity by stromatolites compared to other structures underscores the need to consider a larger role for microbial mats and filaments in carbon fixation and O2 generation during the Archean and Proterozoic.